Laryngeal myofibroblastic tumor: case series and literature review - Alhumaid, Humaid; Bukhari, Manal; Rikabi, Ammar; Farahat, Mohamad; Mesallam, Tamer A.; Malki, Khalid H.; Aldkhyyal, Ahmed (International Journal of Health Sciences, 2011)
Inflammatory myofibroblastic tumor (IMT) or (plasma cell granuloma) of the larynx is a rare benign lesion that usually involves the lungs and broncopulmonary tree, as well as abdominal viscera. Overall this kind of tumor represents less than 1% of all tumors in the lung and respiratory tract with only 31 cases reported to date in the English language literature of laryngeal IMT. We report the first 2 cases in Saudia Arabia of IMT of the larynx treated at King Abdulaziz University Hospital (KAUH) with literature review. Keywords: Inflammatory myofibroblastic tumor - plasma cell granuloma – laryngeal tumors